Mechatronics and Industrial Machines : selected, peer-reviewed papers from the National Conference on Mechanical Engineering and Manufacturing (NCMME 2019), October 18-20, 2019, Ho Chi Minh City, Vietnam - Nguyen, Thanh Nam (Applied mechanics and materials ;, 2020)
This volume contains papers congregated by the result of the National Conference on Mechanical Engineering and Manufacturing (NCMME 2019, 18-20 October 2019, Vietnam). The presented collection is a 2nd part which describes recent developments in the area of mechatronics, robotics, and engineering design. Mechatronics, Robotics, Diesel Engine, Adaptive Control, Autonomous Underwater Vehicle, Extruder Machine, Chain Conveyor, Planar Cam Mechanism General Engineering, Mechanical Engineering, Manufacturing.